Identifying Contextual Factors affecting Hospital In Home Program Implementation within the Veterans Health Administration - Jennifer L Sullivan; Marlena H Shin; Emily Franzosa; A Alex Levine; Jessica Barth; Reza Yousefi-Nooraie; Porooshat Dadgostar; Sunjae Park; Dayna Cooper; Shivani Jindal; Derek D’Arcy; William Hung; et al. (The Gerontologist, 2026)
Abstract Background and Objectives Understanding the factors that enable or hinder successful implementation is essential for improving patient outcomes. Hospital in Home (HiH) programs provide hospital-level care in patients' homes to reduce hospitalization, enhance satisfaction, and improve resource use. Within the Veterans Health Administration (VHA), 14 sites have implemented HiH programs, yet limited research has examined implementation within a large integrated system. This study identifies factors that can support or hinder HiH implementation. Research Design and Methods We conducted interviews with 48 key informants across 14 VHA HiH sites. Guided by the Consolidated Framework for Implementation Research (CFIR) 2.0, we applied directed content analysis using a priori constructs, then developed site-level matrices to summarize findings and compare patterns across sites. Results We identified 18 CFIR constructs—nine that primarily facilitated implementation and nine mixed factors that acted as both facilitators and barriers. Key facilitators included two Individual-level factors (HiH lead capability and motivation, team motivation), one Innovation factor (relative advantage of HiH), and four Implementation Process factors (planning, teaming, reflecting and evaluating, adapting). Mixed factors were mostly within the inner setting, reflecting medical center context, along with two Individual-level mixed factors (leader and recipient motivation). Discussion and Implications HiH programs hold strong potential to transform care for older adults, but success depends on addressing barriers and leveraging facilitators, particularly within the inner setting. Understanding key implementation determinants can enhance adoption, improve outcomes, and strengthen healthcare delivery.